2008
DOI: 10.3748/wjg.14.1067
|View full text |Cite
|
Sign up to set email alerts
|

Infant intestinal Enterococcus faecalis down-regulates infl ammatory responses in human intestinal cell lines

Abstract: AIM:To investigate the ability of Lactic acid bacteria (LAB) to modulate inflammatory reaction in human intestinal cell lines (Caco-2, HT-29 and HCT116). Different strains of LAB isolated from new born infants and fermented milk, together with the strains obtained from culture collections were tested. METHODS:LABs were treated with human intestinal cell lines. ELISA was used to detect IL-8 and TGF-β protein secretion. Cytokines and Toll like receptors (TLRs) gene expression were assessed using RT-PCR. Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
2
36
0
2
Order By: Relevance
“…A multivariate analysis showed that enterococcal colonization was significantly more frequent with enteral feeding than with TPN. In vitro data suggest that GIT enterococci play a beneficial role because some strains of Enterococcus fecalis could suppress the proliferation of intestinal pathogens and thus prevent infection and the induction of inflammation [45]. Conversely, Candida albicans colonization was more frequent in neonates receiving TPN than in neonates receiving enteral feeds, a finding that was similar to previous reports [41,46], but this difference was not significant.…”
Section: Discussionsupporting
confidence: 69%
“…A multivariate analysis showed that enterococcal colonization was significantly more frequent with enteral feeding than with TPN. In vitro data suggest that GIT enterococci play a beneficial role because some strains of Enterococcus fecalis could suppress the proliferation of intestinal pathogens and thus prevent infection and the induction of inflammation [45]. Conversely, Candida albicans colonization was more frequent in neonates receiving TPN than in neonates receiving enteral feeds, a finding that was similar to previous reports [41,46], but this difference was not significant.…”
Section: Discussionsupporting
confidence: 69%
“…Our findings agree with those previously reported by a study performed in Argentina [28]. In contrast, previous studies have shown that TLR4 expression in Caco-2 cells decreased after treatment with lactic acid bacteria [30,31], whereas Miettinen et al [32] found that Lactobacillus rhamnosus GG did not influence TLR4 expression.…”
Section: Discussionsupporting
confidence: 92%
“…L. plantarum also promotes intestinal epithelial homeostasis through an increased viability, as demonstrated by MTT, and inhibits cytokine-induced epithelial cell apoptosis as seen by TUNEL staining (data not shown). It is known that stimulation by commensal bacterial antigens is crucial for the normal development of the mucosal immune system and maintenance of gut homeostasis, but their role in intestinal physiology is incompletely understood [62], although the beneficial effects were consistent with an antiinflammatory state conferred by probiotics [63].…”
Section: Discussionmentioning
confidence: 99%